Potret Diri Irma Fitriyani Amri Sebagai Anak Berkebutuhan Khusus Melalui Karya Serigraphy - IRMA FITRIYANI AMRI, Dr. Yahya, M.Pd., Dra. Minarsih, M.Sn. (Serupa The Journal of Art Education, 2016)
Most people have impression that children with special-need (ABK) cannot perform activities like other normal children. The purpose of this research is to visualize self-figure of children with hearing-disability by serigraphy, where those works are expression of researcher based on self-experience of researcher previously. The processes of these works were performed by filter printing media (serigraphy). The works including: 1) me, 2) feeling1, 3) feeling2, 4) frustration1, 5) frustration2, 6) my heart is listening, 7) I want them to understand, 8) love sign, 9) friend protection, 10) my family. These works proved that children with special-needs have the same feelings with normal children.Keywords : self-figure, serigraphy, graphic.